Effect of obesity on cognitive function: a cross-sectional study - Gandhi, Piyush P.; Humaney, Nalini R. (International Journal of Research in Medical Sciences, 2022)
Background: Obesity is the leading cause of many health problems. It mostly affects the brain by cerebrovascular events, but since it is a chronic low-grade inflammatory state, inflammatory cytokines in blood alter neuronal function. The jolly-fat hypothesis says that obese people have better cognition as they have more fat storage which is required to make neurotransmitters. Many studies have been done to support each of the above hypotheses but most are done in the paediatric or geriatric populations which can have other confounding factors. Obesity can be easily treated with proper dietary interventions, exercise, pharmaceutical therapies, or surgical interventions. Thus, it was worth exploring as simple lifestyle changes might lower the incidence of cognitive disabilities. Methods: This study was done on undergraduate medical students with a sample size of 120 (60 male and 60 female). Their body mass index was calculated after taking body weight and height. The cognition of subjects was studied using the Washington click reaction time test. This was correlated with body mass index using a t test to find a p value with a level of significance of 0.05. Results: High body mass index is associated with poor cognition as the p<0.05 (0.025006). There was no role of gender on body mass index or cognitive functions. Conclusions: Obesity does affect the cognitive function in healthy adult populations with no comorbidities irrespective of the gender of the individual. More prospective studies with a more sensitive battery of tests can be done to further understand this.